Allosensibilisation to erythrocyte antigens (literature review) - N. V. Mineeva; I. A. Pashkova; I. I. Krobinets; E. A. Sysoeva (Онкогематология, 2015)
In this article literature review of the causes of allosensibilisation to erythrocyte antigens are presented. It is shown that the ability to produce antierythrocyte antibodies is affected by many factors, principal of whom it is difficult to identify. For the allosensibilisation development requires genetically determined differences in erythrocyte antigens phenotypes of donor and recipient, mother and fetus, which can lead to immune response and antibodies production. The biochemical nature of erythrocyte antigens, antigen dose (the amount of transfused doses, the number of antigens determinants on donor and fetus erythrocytes, the number of pregnancies) are important. Individual patient characteristics: age, gender, diseases, the use of immunosuppressive therapy and the presence of inflammatory processes, are also relevant. Note that antibody to one erythrocyte antigens have clinical value, and to the other – have no. The actual data about frequency of clinically significant antibodies contribute to the development of post-transfusion hemolytic complications prophylaxis as well as the improvement of laboratory diagnosis of hemolytic disease of the newborn in the presence of maternal antierythrocyte antibodies.